2019
DOI: 10.25165/j.ijabe.20191205.4289
|View full text |Cite
|
Sign up to set email alerts
|

An effective spray drift-reducing method for a plant-protection unmanned aerial vehicle

Abstract: A spraying system for a plant-protection unmanned aerial vehicle (UAV) was designed to reduce spray drift. A custom low-speed wind tunnel was constructed to generate a wind speed ranging from 0 to 5.92 m/s. The results showed that the wind speed was attenuated with an increase in distance. To compensate for the attenuation, a linear-fitting model was adopted. Then, the relationship between the spraying pressure and atomization rate was analyzed, and a fuzzy algorithm was adopted to adjust the spraying angle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“… Zhu et al (2010) used a PWM controller to achieve high-precision spray. Chen et al (2019) proposed a spray system that can adjust the spray angle and pressure according to the wind speed and its changes to reduce droplet drift. Akkoyun (2019) improved the spray range and reduced the use of pesticides by changing the nozzle distribution on the UAV’s boom.…”
Section: Techniques For Improving the Deposition Effectmentioning
confidence: 99%
“… Zhu et al (2010) used a PWM controller to achieve high-precision spray. Chen et al (2019) proposed a spray system that can adjust the spray angle and pressure according to the wind speed and its changes to reduce droplet drift. Akkoyun (2019) improved the spray range and reduced the use of pesticides by changing the nozzle distribution on the UAV’s boom.…”
Section: Techniques For Improving the Deposition Effectmentioning
confidence: 99%
“…Spray drift is considered to be one of the bottlenecks and biggest problems for pesticide application technology . Drift leads to damage to susceptible off-target species, reduces the effectiveness of the pesticide, and leads to environmental contamination . For example, herbicide glyphosate spray-drift has a long-term effect on the phenotypic response such as seed size and shoot length and might lead to adaptations and cascading ecological impacts.…”
Section: Future Prospects and Conclusionmentioning
confidence: 99%
“…Many researchers have conducted a lot of research on the drift phenomenon and its influencing factors, including the spray parameters [13,14], airflow parameters [15,16], and other factors [17]. By analyzing the droplets' drift process, Felsot [18] concluded that the main factors were the spray method and droplet size and proposed that protective shields and buffer zones should be used to reduce droplet drift.…”
Section: Introductionmentioning
confidence: 99%